Comparison of mNGS with conventional methods for diagnosis of cryptococcal meningitis: a retrospective study - Zai-Jie Jiang; Jian-Chen Hong; Bi-Wei Lin; Wei-Qing Zhang; Qi-Chao Fan; Bi-Hui Yang; Xiang-Ping Yao (Scientific Reports)
Abstract The application of metagenomic next-generation sequencing (mNGS) in the diagnosis of cryptococcal meningitis is relatively under characterized. Here, we retrospectively evaluated data from cryptococcal meningitis patients who were tested using mNGS and/or routine testing, including fungal culture, India ink staining, and cryptococcal antigen (CrAg) testing. The performance of mNGS was then assessed. Initial cerebrospinal fluid (CSF) samples were collected from 65 patients with suspected central nervous system (CNS) infection and tested using conventional tests and/or mNGS. mNGS offers a culture-independent approach, facilitating a rapid and unbiased detection of a broad spectrum of pathogens. Patients with bacterial tuberculous or viral meningitis were used as mNGS-positive controls and one autoimmune encephalitis patient was used as an mNGS-negative control. In the 45 patients diagnosed with cryptococcal meningitis, the sensitivity, specificity, positive predictive value, negative predictive value, and concordance rate of mNGS were 92%, 100%, 100%, 90.9%, and 95.6%, respectively. Compared to conventional methods, the sensitivity of mNGS was slightly lower than CrAg tests (96.7%) but higher than India ink (79.5%) and culturing (63.4%). Of the two negative mNGS cases (2/25, 8.0%), one was positive by India ink staining, culture, and CrAg testing, while the other was positive only by CrAg testing. A combination of mNGS and conventional methods enhanced the detection rate to 100%. Our study demonstrates that both CrAg and mNGS offer excellent diagnostic accuracy for cryptococcal meningitis, and utilizing both tests can enhance clinical assessment and patient management.